PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN SATUAN PENGAMANAN PT GARDA UTAMA NASIONAL AREA TUGAS BANK BCA MENARA BIDAKARA JAKARTA SELATAN - Salza Amelya Febriana; Heri Priyanto (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the significant influence of organizational culture and compensation on the performance of employees of the PT Garda Utama Nasional security unit in the BCA Tower Bidakara South Jakarta area. The research method used in this research is a quantitative method. The sampling technique used was saturated sampling, namely using a sample of 53 respondents. The data collection method used is the questionnaire method. Data processing uses the SPSS Version 26 program. The data analysis technique used is statistical analysis by testing validity tests, reliability tests, classical assumption tests, simple linear regression tests, multiple linear regression tests, coefficient of determination, test t hypothesis and f hypothesis test. The research results of organizational culture have a significant effect on employee performance, shown by the simple linear regression equation Y = 28.135 + 0.330X1, this is also proven by hypothesis testing and the t value obtained > t table (3.795 > 1.675). The research results show that compensation has a significant effect on employee performance, shown by the simple linear regression equation Y = 22.844 + 0.457X2, this is also proven by hypothesis testing and the t value obtained > t table (4.822 > 1.675). Results of research on organizational culture and compensation on the performance of security unit employees at PT Garda Utama Nasional, Bank BCA Tower Bidakara South Jakarta's assigned area. shown by the multiple linear regression equation Y = 21.208 + 0.140X1 + 0.356X2. This is also proven by the results of the hypothesis test and the calculated f value > f table (12.733 > 3.183). The results of the coefficient of determination test for the variables organizational culture (X1) and compensation (X2) have an influence of 33.7% on the performance of security unit employees at PT Garda Utama Nasional in the area assigned to Bank BCA, Menara Bidakara, South Jakarta. Thus, H0 is rejected and Ha3 is accepted, meaning that it is proven that there is a positive significant simultaneous influence between organizational culture (X1) and compensation (X2) on employee performance (Y).